Effects of water and salt coordinated regulation at the different growth stages on water consumption and yield of tomato - Wang, Weihua; Gong, Yidan (International Journal of Agricultural and Biological Engineering, 2021)
The objective of this study was to explore the effects of different degrees of water and salt stress on the actual water consumption and soil salt accumulation of tomatoes and the salt tolerance characteristics of tomatoes under brackish water combined with regulated deficit irrigation mode. The greenhouse pot experiment was used to set three influencing factors, the irrigation water salinity S1 was 1.1 g/L (local shallow groundwater), S2 was 2.0 g/L, and S3 was 4.0 g/L, respectively, and different degrees of water deficit (W1 ranged from 65%-75% Field Capacity (FC), W2 ranged from 55%-65% FC, W3 ranged from 45%-55% FC) and seedling stage (T1), blossoming and bearing fruits stage (T2) and mature picking stage (T3). The response of fresh fruit weight, stems and leaves weight, yield and water use efficiency of tomato under water and salt stress were monitored and analyzed. The results showed the coordinated regulation of water and salt can significantly reduce the electrical conductivity of the 0-30 cm soil of the tomato root system. The higher the salinity of irrigation water, the better the salt control effects of the coordinated regulation of water and salt; the coordinated regulation of water and salt at different growth stages had significant effects on the weight of fresh tomato fruits, the weight of stems and leaves and the yield. The salinity of irrigation water was in inverse proportion to the yield of tomatoes; In S1 treatment irrigation (irrigation water salinity was 1.1 g/L) under the mildly regulated deficit in the seedling stage (irrigation water was 55%-65% of the field water capacity) can effectively reduce the irrigation water volume during the whole growth stage while ensuring that there was no significant reduction in yield. The research results provided a scientific and reliable theoretical basis for the increase of local tomato production, the improvement of water use efficiency and the formulation of suitable irrigation patterns.Keywords: tomato, coordinated regulation of water and salt, soil electrical conductivity, water consumption, yieldDOI: 10.25165/j.ijabe.20211404.6238Citation: Wang W H, Gong Y D. Effects of water and salt coordinated regulation at the different growth stages on water consumption and yield of tomato. Int J Agric & Biol Eng, 2021; 14(4): 96–105.